Software Business Third International Conference, ICSOB 2012, Cambridge, MA, USA, June 18-20, 2012. Proceedings - Cusumano, Michael A.; Iyer, Bala.; Venkatraman, N.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book contains the refereed proceedings of the Third International Conference on Software Business (ICSOB) held in Cambridge, MA, USA, in June 2012. The software business refers to commercial activities in the software industry, aimed at generating revenues from the design, delivery, and maintenance of software products and IT services to enterprises and individual customers, as well as from digital content. Although this business shares common features with other knowledge-intensive markets, it carries many inherent features making it a challenging domain for research. The 20 full and 10 short papers accepted for ICSOB were selected from 60 submissions and are organized in sections on software product management, organizational transformation, industry transformation, software platforms and ecosystems, and emerging trends.
Keywords: Computer science; Software engineering; Computer industry; Information Systems; Computer Science; The Computer Industry; Management of Computing and Information Systems; Innovation/Technology Management; Software Engineering; Project Management